Tanggapan Terhadap Kami No Shiten dan Mushi No Shiten No Gengo Bunka dari Prof. Someya Yoshimichi - Sheddy N. Tjandra (Bina Nusantara University, 2013)
This is a preliminary study about Japanese conception of the world’s language and culture. Prof. Someya Yoshimichi, emeritus professor from Shizuoka Unversity Japan, in an international conferene on Japanese studies held at Universitas Nasional Jakarta on February 2012, has pointed out that the present world’s language and culture can be divided into two categories. One is God’s Language and Culture, and the other is Insect’s Language a Culture. According to him, the God’s Language and Culture is mainly from European and American (Europe), and the Insect’s Laguage and Culture is mainly from Asian especially from Japan and South-east Asia. The writer does not understand why the Japanese takes God and Insect as a pair of contrastive culture. Therefore, the writer collected data from Indonesian indigenous culture, mainly from public beliefs and religions to argue about the Japanese pair of contrastive culture. This writing uses qualitative interpretation method (hermeneutics) and a method of descriptive analysis to understand Indonesian data, and to present the results of interpretation. For previous studies, the writer took the Japanese and Chinese In-yooron to check the realities of Japanese conception, and also took hipernym and hyponym theory from semantics to check the contrastive meaning of the word God and Insect. In short, the writer sees that God and Insect are not an antonym, and also have no contrastive meaning in any sense of semantics and logics.